Influence of Cryopreserved and Freshly Isolated Placental Explants and Cells - Conditioned Media on Murine Uterine and Ovarian Organotypic Cultures - Prokopiuk, Volodymyr Yu. (Problems of Cryobiology and Cryomedicine, 2018)
The methods of cell and tissue therapy, the promising objects of those are the placental derivatives, affecting namely female reproductive system and the levels of its regulation, have been widely applied in current reproductive medicine. The mechanisms of this interaction have still remained unclear. We studied here the influence of the media, conditioned with cryopreserved and freshly-isolated placental cells and explants on isolated murine ovarian, uterine cultures and that of fibroblasts. The cultures were evaluated using morphological methods and metabolic tests. Conditioned media were shown to stimulate metabolic activity of the uterine culture and to suppress it in ovarian culture. No fibroblast response to these media testifies to a direct influence of placental humoral factors on ovarian generative elements and endometrium, but not through the elements of connective tissue. The features of the media, conditioned with the native and cryopreserved placental cells and explants were established as not significantly different. Probl Cryobiol Cryomed 2018; 28(2): 139–150